Diagnostic dilemmas in young onset diabetes mellitus - Avijit Saha; Parna Roy (Annals of Medical Science and Research)
The prevalence of diabetes among teenagers is increasing worldwide. Diabetes in young has profound implications on long term health of individuals and for the society as well. A wide range of specific type of diabetes can occur in this age group. The diagnosis of diabetes actually involves two steps. The first step is to document the elevated blood glucose as per the autoimmune diabetes in adults cutoffs and the second step is to characterize the type of diabetes the particular person has. The diagnosis of specific type of diabetes in young individuals poses several unique challenges. The things get further complicated by the fact that Asian-Indians represent diverse ethnicity where Type 2 diabetes tends to occur two decades earlier and relatively at lower body mass index. Treatment outcome depends on the correct diagnosis of diabetes type and subsequent targeted therapy. Correct diagnosis also enables clinicians to provide information to the patient about disease course and nature of therapy that the particular patient needs. A detailed patient history and physical examination provide clues to the diagnosis. However, to make appropriate diagnosis, sometimes, we need to take the help of special tests such as islet cell autoantibodies, fasting and stimulated c-peptide, lipid profile, USG of the abdomen, and homeostatic model assessment of insulin resistance. The results of these tests need to be interpreted cautiously as many of these tests' results cannot reliably discriminate between types of diabetes and moreover results are keep changing as the disease evolves. In this review, we discuss the characteristics of each type of diabetes that can occur in young individuals.